Teaching health professionals how to tailor gender-affirming medicine protocols: A design thinking project - MacKinnon, Kinnon R. (Perspect Med Educ, 2020)
BACKGROUND: Content knowledge surrounding transgender (trans) medicine is currently lacking in the formal medical education curricula. Evidence indicates that the main protocols used to assess and refer trans patients for gender-affirming medicine are misunderstood by health professionals, and require flexible adaptation to achieve health equity and patient-centred care. APPROACH: A free online educational tool for gender-affirming medicine, The Path to Patient-Centred Care, was developed to teach learners how to adapt assessment protocols. Resource creation was supported by a knowledge translation grant that endorsed design thinking, a human-centred and solutions-focused framework recommended for use in curriculum development. EVALUATION: The Path to Patient-Centred Care provides learners with information related to key principles of patient-centred care in gender-affirming medicine, including a guide on how to adapt the main assessment protocols to achieve equitable care. The curriculum also includes narratives from trans patients and health professionals that focus on health equity, and a clinical vignette about a complex case, designed to foster critical thinking on medical ethics. Project future directions involve an implementation and evaluation pilot study with a diverse group of continuing professional development medical learners using a mixed-methods program evaluation design. REFLECTION: The use of design thinking to develop this resource exemplifies a novel approach to curriculum development. By using pedagogical strategies that foster critical reflection, this innovative online education tool strives to teach self-directed learners how to provide care that emphasizes trans people’s self-determination and autonomy in medical decision-making.